Kecemasan Berbahasa Asing Anak Sekolah Dasar Dalam Pembelajaran Bahasa Inggris - I Putu Yoga Purandina (STAHN Mpu Kuturan Singaraja, 2022)
This study explores the foreign language anxiety of elementary school children in learning English in elementary schools in Marga District, Tabanan. English is a local content learning. The result is as follows. Researchers found how the occurrence of student anxiety in learning English and the factors that cause it. In general, this is due to (1) the lack of time allocation for them to get English lessons, (2) they get more theory in class than they get direct practice in the field, (3) they rarely use English because in the family and society they rarely do it. Communication in English. Then specifically, the factors that cause them to be anxious are (1) Their lack of confidence in using English, (2) Fear of negative judgments, and (3) Fear of being inferior to friends or fear of being compared to friends.